The Tijani method: origin and development - ZIZAH, Saida (Social Sciences Journal)
The Ottoman era in Algeria was characterized by the spread of Sufi orders, and from this article, in which we dealt with the most widespread Sufi order in Algeria, namely the Tijani order. And its extension of principles, educational and social functions, and its relationship to other Sufi orders